2019
DOI: 10.1093/nar/gkz118
|View full text |Cite
|
Sign up to set email alerts
|

Labelled regulatory elements are pervasive features of the macrophage genome and are dynamically utilized by classical and alternative polarization signals

Abstract: The concept of tissue-specific gene expression posits that lineage-determining transcription factors (LDTFs) determine the open chromatin profile of a cell via collaborative binding, providing molecular beacons to signal-dependent transcription factors (SDTFs). However, the guiding principles of LDTF binding, chromatin accessibility and enhancer activity have not yet been systematically evaluated. We sought to study these features of the macrophage genome by the combination of experimental (ChIP-seq, ATAC-seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…We are unsure why this is the case. While searching for transcription factors bound by HDAC3, we observed in the data published by Czimmerer et al that HDAC3 bound upstream of the IκBα-encoding genes Nfkbiz and Nfkbia in mice, both of which were also upregulated in HDAC3i pre-treated macrophages ( Supplemental Figures 6A, B ) ( 51 , 52 ). As IκBα protein prevents NFκB nuclear translocation and gene expression in both in human and mice, we speculate that this mechanism explains how HDAC3 negatively regulates NFκB activity and that HDAC3i reduces expression of NFkB dependent pro-inflammatory genes as measured in this study.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…We are unsure why this is the case. While searching for transcription factors bound by HDAC3, we observed in the data published by Czimmerer et al that HDAC3 bound upstream of the IκBα-encoding genes Nfkbiz and Nfkbia in mice, both of which were also upregulated in HDAC3i pre-treated macrophages ( Supplemental Figures 6A, B ) ( 51 , 52 ). As IκBα protein prevents NFκB nuclear translocation and gene expression in both in human and mice, we speculate that this mechanism explains how HDAC3 negatively regulates NFκB activity and that HDAC3i reduces expression of NFkB dependent pro-inflammatory genes as measured in this study.…”
Section: Discussionmentioning
confidence: 76%
“…To understand whether HDAC3 directly affects transcription of TFs, we analyzed ChIP-sequencing data on HDAC3 binding in mouse M-CSF differentiated bone marrow derived macrophages (BMDMs) obtained from GSE106701 ( 51 , 52 ). Combining the reported peaks from samples GSM2845618 and GSM2845619 with the differential expression analysis on TFs indicated that mouse orthologs of the differentially expressed TF genes HIVEP2 , ELK3 , IRF7 , NFKB1 , ARID5B , REL , KLF7 , ETV3 and MXD1 were bound by HDAC3, with one peak associated to the intergenic region of HIVEP2 belonging to the top 2.5% strongest peaks ( Figure 6C and Supplemental Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The macrophage subset-specific enhancer repertoires serve as a binding platform for the signal-dependent transcription factors (SDTFs). Many microenvironmental signals including pathogenderived molecules, cytokines, and lipids can activate SDTFs turning on signal-specific gene expression programs (29)(30)(31)(32). Toll-like receptor (TLR) ligands such as LPS and poly(I:C) as well as tumor necrosis factors (TNFs) activate nuclear factor kappa-lightchain-enhancer of activated B cells (NFkB) and Activator protein 1 (AP-1) transcription factor complexes initiating a transcriptional program of the inflammation (33,34).…”
Section: Transcriptional Basis Of Macrophage Heterogeneity and Plastimentioning
confidence: 99%